2019
DOI: 10.1101/gad.320663.118
|View full text |Cite
|
Sign up to set email alerts
|

Helix–loop–helix proteins and the advent of cellular diversity: 30 years of discovery

Abstract: Helix-loop-helix (HLH) proteins are dimeric transcription factors that control lineage-and developmental-specific gene programs. Genes encoding for HLH proteins arose in unicellular organisms >600 million years ago and then duplicated and diversified from ancestral genes across the metazoan and plant kingdoms to establish multicellularity. Hundreds of HLH proteins have been identified with diverse functions in a wide variety of cell types. HLH proteins orchestrate lineage specification, commitment, self-renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 202 publications
(282 reference statements)
2
114
0
Order By: Relevance
“…70 amino acids) and is a strict pre-requisite for DNA binding, mediated by the short basic region (15 a.a.) that precedes the HLH (Amati et al, 1992, Blackwood & Eisenman, 1991. In line with those biochemical findings, structural studies on DNA-bound or free dimers, including Myc/Max (Nair & Burley, 2003, Sammak et al, 2019, Max/Max (Brownlie et al, 1997, Ferre-D'Amare et al, 1993, Sauvé et al, 2007, Sauvé et al, 2004 and other bHLH proteins (Murre, 2019), showed that dimerization allows positioning of the basic regions for insertion into the DNA major groove (Fig. EV1A).…”
Section: Structure-based Mutagenesis Of the Myc Dna-binding Domainsupporting
confidence: 65%
“…70 amino acids) and is a strict pre-requisite for DNA binding, mediated by the short basic region (15 a.a.) that precedes the HLH (Amati et al, 1992, Blackwood & Eisenman, 1991. In line with those biochemical findings, structural studies on DNA-bound or free dimers, including Myc/Max (Nair & Burley, 2003, Sammak et al, 2019, Max/Max (Brownlie et al, 1997, Ferre-D'Amare et al, 1993, Sauvé et al, 2007, Sauvé et al, 2004 and other bHLH proteins (Murre, 2019), showed that dimerization allows positioning of the basic regions for insertion into the DNA major groove (Fig. EV1A).…”
Section: Structure-based Mutagenesis Of the Myc Dna-binding Domainsupporting
confidence: 65%
“…Stem cells and cancer cells share a lot of similarities in gene expression, cellular processes and signal transductions, but there are not many studies researching the effects of HIF-TWIST on normal stem cells. Recent studies have shown that E2A and TWIST both belong to the bHLH protein family [15]. E2A can activate the expression of cyclin-dependent kinases (CDKs) inhibitor p21 gene [16,17]; p21 also plays an important role in the differentiation of osteoblasts and myoblasts [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Basic Helix-Loop-Helix (bHLH) proteins are currently recognized as the most important class of transcription factors. They can form specific interactions with the genetic cis-elements of eukaryotes, thereby activating or inhibiting the transcription and translation of the gene and they may also bind to the DNA binding proteins with activation or inhibition activities (Murre et al, 1989;Murre, 2019). They can combine with other transcription factors to form a complex genetic regulatory network too (Murre et al, 1989;Atchley and Fitch, 1997;Boggon et al, 1999;Luscombe et al, 2000;Riechmann et al, 2000;Stevens et al, 2008;Murre, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They can form specific interactions with the genetic cis-elements of eukaryotes, thereby activating or inhibiting the transcription and translation of the gene and they may also bind to the DNA binding proteins with activation or inhibition activities (Murre et al, 1989;Murre, 2019). They can combine with other transcription factors to form a complex genetic regulatory network too (Murre et al, 1989;Atchley and Fitch, 1997;Boggon et al, 1999;Luscombe et al, 2000;Riechmann et al, 2000;Stevens et al, 2008;Murre, 2019). At present, members of the bHLH transcription factor family are found to be crucial and they play many important roles in the cell proliferation and differentiation, body immunity, muscle tissue formation, neurons, resistance to stress, development of the eye and intestine, hematopoietic function and coagulation function, adaptation to hypoxic environment, sex determination and the process of genetic development of animals and plants (Murre et al, 1989;Murre, 2019;Atchley and Fitch, 1997;Boggon et al, 1999;Luscombe et al, 2000: Riechmann et al, 2000Stevens et al, 2008;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%